El canto del Ruiseñor: aproximación a las nociones de universal y particular en Borges - Rodríguez Martín, María del Carmen (THÉMATA. Revista de Filosofía, 2015)
El objetivo es mostrar cómo a partir de la lectura de Schopenhauer Borges revisa su concepción de la Teoría de las Ideas platónicas deteniéndonos en las nociones de particular y universal –individuo y especie- y las relaciones de éstos conceptos con el problema de la identidad a partir de la formulación del “principio ontológico” por el cual un hombre es todos los hombres. Though Borges is not very fond of the “museum of platonic ideas”, my aim is to show how he turns to Schopenhauer in order to revise the theory of forms. The ideas and the individuals interact as the whole and the part. The individuals manifest the unity of idea in a plural way and function at the same time as the objectification of the will. On the other hand, I denominate the “ontological principle”, the principle adopted by Borges from Schopenhauer in order to confer the primacy to the species and the universal over the individuals and the particular. The individual makes a part of the species, that is, one person represents all the persons.